Explanation:
sin^2x = 2cotx sin^2x
Rewrite right side as fractions:
sin^2x =
*
*
![((sinx)(sinx))/(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hcnm9tf4q28ms3mhyb05wrb0pbejcthgr8.png)
Multiply together
and
:
sin^2x =
*
![((cosx)(sinx)(sinx))/(sinx)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7vddd203l9mg3npxc9gn2jhwh43vakbmi0.png)
Cancel out sinx on top and bottom:
sin^2x =
*
![((sinx)(cosx))/(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lnmihih506esd8ejq44l0mgm1wjxmjvbe3.png)
Multiply together 2 and (sinx)(cosx):
sin^2x = 2sinxcosx
Substitute sin^2x in for 2sinxcosx:
sin^2x = sin^2x